2015
DOI: 10.1073/pnas.1505463112
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary comparison reveals that diverging CTCF sites are signatures of ancestral topological associating domains borders

Abstract: Increasing evidence in the last years indicates that the vast amount of regulatory information contained in mammalian genomes is organized in precise 3D chromatin structures. However, the impact of this spatial chromatin organization on gene expression and its degree of evolutionary conservation is still poorly understood. The Six homeobox genes are essential developmental regulators organized in gene clusters conserved during evolution. Here, we reveal that the Six clusters share a deeply evolutionarily conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(161 citation statements)
references
References 42 publications
11
150
0
Order By: Relevance
“…It had been shown (Nora et al 2012) that deletion of a TAD boundary in the neighborhood of the Xist locus on the X chromosome could result in ectopic long-range contacts and overall misregulation of expression. Recent analysis of the Six homeodomain locus of zebrafish (Gomez-Marin et al 2015) revealed the presence of oriented CTCF sites (shown in that study as divergent between adjacent TADs and therefore convergent within TADs) at TAD boundaries; deletion of one of these boundaries in BACs leads to inappropriate interdomain enhancer-promoter interactions. Similarly, CRISPR/Cas-mediated deletion of a CTCF site within the Hox clusters in mouse ES cells disrupts a topological boundary, resulting in activation of previously silent Hox genes.…”
Section: Convergence Is Criticalmentioning
confidence: 90%
“…It had been shown (Nora et al 2012) that deletion of a TAD boundary in the neighborhood of the Xist locus on the X chromosome could result in ectopic long-range contacts and overall misregulation of expression. Recent analysis of the Six homeodomain locus of zebrafish (Gomez-Marin et al 2015) revealed the presence of oriented CTCF sites (shown in that study as divergent between adjacent TADs and therefore convergent within TADs) at TAD boundaries; deletion of one of these boundaries in BACs leads to inappropriate interdomain enhancer-promoter interactions. Similarly, CRISPR/Cas-mediated deletion of a CTCF site within the Hox clusters in mouse ES cells disrupts a topological boundary, resulting in activation of previously silent Hox genes.…”
Section: Convergence Is Criticalmentioning
confidence: 90%
“…As the DNA recognition sequence of CTCF is not palindromic, it can be regarded as having a forward (F) or reverse (R) orientation, which implies that pairs of CTCF sites at the base of a loop theoretically can have four different relative orientations: FF, RR, FR, and RF (Rao et al 2014). In line with the importance of relative CTCF-binding site orientation, motif orientation is often conserved among distinct species, particularly at conserved domain boundaries (Vietri Rudan et al 2015), and boundaries often harbor pairs of divergently oriented CTCF-binding motifs (Gomez-Marin et al 2015). Thanks to the advent of CRISPR/Cas9 genome editing, the observed dependence of CTCF-mediated looping on motif orientation could be validated.…”
Section: Ctcf-and Cohesin-mediated Architectural Loops Surrounding Tadsmentioning
confidence: 99%
“…ATAC-seq data and CTCF sites were reported (34,35). Open chromatin regions with peak intensity more than 10 (arbitrary units) and without overlapping CTCF sites were regarded as primary candidates for potential enhancers.…”
Section: Methodsmentioning
confidence: 99%
“…We used recently published ATAC-seq (Assay for Transposase-Accessible Chromatin) data from whole zebrafish embryos at 24 h after fertilization (hpf) to assess open chromatin regions as sites of putative enhancers (34). In addition, we inspected predicted CTCF (CCCTC-binding factor) sites in the open chromatin regions (35). Because these sites are involved in the formation of chromatin loops, we prioritized open chromatin regions without CTCF sites.…”
Section: Significancementioning
confidence: 99%